O desenho animado como brincadeira e brinquedo na educação infantil - Schwarzinger, Camila Biasotto de Araujo (2019)
The influence of cartoons on children is a recurring theme in research over the last decades, which demonstrates a concern with the quality of what is produced and exhibited, especially on television. Studies in the area of education focus on the effects that cartoons have on children's interactions and on the messages that are conveyed to children. When they address the school scenario, they often refer to the role of teachers as facilitators and the use they make of cartoons as a pedagogical resource. This research, linked to the field of teacher training, aims to investigate the place occupied by cartoons in Early Childhood Education, based on the following questions: Are cartoons used as toys by teachers and children? How do children reinterpret cartoons at the time of playing? How are cartoons incorporated/translated into play? What place do they occupy in the teachers' planning and in the School Plan? To carry out the research, the qualitative approach has been followed. The teachers of Early Childhood Education 3 and 4 and the children of Early Childhood Education 3, 4 and the first year of elementary school were interviewed. The teachers' weekly plans for the year 2017, textbooks and the School Plan were also analyzed and field observation was performed. The theoretical framework is based on the issues of the notion of toys, games and cartoons in Early Childhood Education, with the contribution of the following authors regarding the development of children, cartoons and playful cultures: Montessori (2010), Wallon (2010), Malaguzzi (2016), Kishimoto (2016), Brougère (1998), Pacheco (1998), Huizinga (1996) and Dornelles (2001). The results revealed that teachers utilize cartoons as a pedagogical resource to complement content, serving as a strategy to teach some of the weekly plans' propositions.